Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

solve for d

-6 - d = 6 - 4d


Sagot :

Answer:

d = 4

Step-by-step explanation:

- 6 - d = 6 - 4d ( add 4d to both sides )

- 6 + 3d = 6 ( add 6 to both sides )

3d = 12 ( divide both sides by 3 )

d = 4